Hepatic, testicular and spermatozoa antioxidant status in rats chronically treated with Garcinia kola seed (2013)
Ethnopharmacological relevance: Garciniakola seed is commonly used in African Traditional Medicineas a remedy for liver disorders, hepatitis, bronchitis, throat infections as well as an aphrodisiac and fertility enhancing substance. Owing to the abundance of complex mixture of phenolic compounds in Garciniakola seed, there is a growing safety concern on its long-term use in folklore medicine.The present study evaluated the hepatic, testicular and spermatozoa antioxidant status in rats chronically treated with Garciniakola seed. Materials and methods: Adult male Wistar rats were randomly assigned to four groups of 10rats each and were orally administered with Garciniakola at 0, 250, 500 and 1000mg/kg for 6 consecutive weeks. Clinical observations, serum biochemistry, oxidative stress biomarkers, spermatozoa parameters and histopathological examination of the organs were assessed to monitor treatment-related adverse effects in rats. Results: Long-term treatment of Garcinia kola had no adverse effect on the spermatozoa characteristics but significantly elevated testosterone concentration when compared to the control group. Improvement of antioxidant systems was accompanied by a significant decrease in malondialdehyde level in the liver, testes and spermatozoa of Garciniakola treated rats. Histological observation revealed that chronic administration of Garciniakola had no effect on the liver and testes at all doses when compared with control. Conclusion: Garciniakola seed boosts the antioxidant status and exhibits no adverse effect on the liver, testes and spermatozoa after a long-term oral exposure in rats.